2005
DOI: 10.1177/0020872805057087
|View full text |Cite
|
Sign up to set email alerts
|

Violence in the social work workplace

Abstract: There is a growing literature on client violence against social workers. Studies conducted in the UK, the USA and Canada have provided data on the nature and prevalence of clients' violence against social workers, on the psychological impact of violence against social workers, on the type of client most likely to initiate violence and on the types of settings and situations in which client violence is most likely to occur (Astor et al.. To date, however, comparatively few studies have examined social workers' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 9 publications
0
58
0
1
Order By: Relevance
“…However, the design of this study does not allow for generalization of this rate to all mental health nurses (Ashmore et al 2006). As noted earlier, a survey of 171 social workers found that 16.3% reported being stalked at some point in their careers (MacDonald and Sirotich 2005). While methodological issues, including self-selection bias of some of the survey studies, may account for variable rates of stalking reported, clearly this is an issue of significant concern for all mental health practitioners.…”
Section: The Incidence Of Stalkingmentioning
confidence: 92%
See 1 more Smart Citation
“…However, the design of this study does not allow for generalization of this rate to all mental health nurses (Ashmore et al 2006). As noted earlier, a survey of 171 social workers found that 16.3% reported being stalked at some point in their careers (MacDonald and Sirotich 2005). While methodological issues, including self-selection bias of some of the survey studies, may account for variable rates of stalking reported, clearly this is an issue of significant concern for all mental health practitioners.…”
Section: The Incidence Of Stalkingmentioning
confidence: 92%
“…A Canadian random survey of 171 social workers found that 16.3% reported being stalked at some point in their careers (MacDonald and Sirotich 2005). Other surveys while not specifically addressing stalking behavior, report high rates of threats and actual harm to social workers by clients (MacDonald and Sirotich 2001;Newhill 1996;Rey 1996;Regehr et al 2004).…”
mentioning
confidence: 99%
“…Social workers are expected to work in adverse situations and be able to functionally provide necessary services to client populations and communities. For instance, some social workers have to practice in situations where physical violence and emotional fatigue are common outcomes of any given day of practice (Macdonald & Sirotich, 2005;Smith, 2006Smith, , 2007. All of these factors, and the inadequate salaries they are forced to accept, bear heavily on practitioners' SWB.…”
Section: Coping In Adverse Situationsmentioning
confidence: 99%
“…In addition to coping with the negative effects of therapy work (Linley & Joseph, 2007), fending off compassion fatigue, burnout and vicarious trauma from exposure to their clients' tremendously stressful experiences (Jenkins & Baird, 2002;Kim & Stoner, 2008) and facing elements of risk and danger including actual and threatened violence (Macdonald & Sirotich, 2005;Smith, 2006Smith, , 2007, social workers must also try to meet their own objectives and manage the expectations they and others have about their work settings. Understanding the complex pressures and effects of social work professional expectations on social worker well-being is crucial in developing more successful methods of social worker recruitment and retention, education and practice (Stevens et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…MacDonald and Sirotich (2005) collected data on Canadian social workers' experiences with workplace violence. Their data indicated that about 56.1 percent of the sample was verbally harassed and 19.6 percent had been threatened with physical harm over the last two years.…”
Section: Previous Researchmentioning
confidence: 99%